2001
DOI: 10.2224/sbp.2001.29.7.687
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy and Academic Performance

Abstract: The aim in the present study was to examine the predictive effectiveness of self-efficacy in an academic setting. Seventy-six postgraduate students completed a questionnaire to assess efficacy expectations toward competencies perceived to underpin performance on the course. As there was a 13-week difference in time between completing the self-efficacy questionnaire and completing the performance criterion, it was considered important to assess the stability of self-efficacy measures. To this end, participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
1
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 13 publications
8
87
1
10
Order By: Relevance
“…Baker, 2009). Likewise, research has shown that students' self-efficacy (e.g., Bandura, 1997;Lane & Lane, 2001;Hsieh, Sullivan, & Guerra, 2007;Weiser & Riggio, 2010), study motivation (Areepattamannil, 2012), developed self-regulation (e.g., Tuijula, 2011;Zimmerman, 1990), and optimistic thinking and action (e.g., Hoy, Tarter, & Woolholk Hoy, 2006;Nonis & Wright, 2003) have a clear connection with the smoothness of upper secondary education studies. Learning-oriented students emphasize the mastery of learning new things and contents when referring to their school-related aspirations.…”
Section: Theoretical Background: Studies On Smooth Study Paths In Uppmentioning
confidence: 99%
“…Baker, 2009). Likewise, research has shown that students' self-efficacy (e.g., Bandura, 1997;Lane & Lane, 2001;Hsieh, Sullivan, & Guerra, 2007;Weiser & Riggio, 2010), study motivation (Areepattamannil, 2012), developed self-regulation (e.g., Tuijula, 2011;Zimmerman, 1990), and optimistic thinking and action (e.g., Hoy, Tarter, & Woolholk Hoy, 2006;Nonis & Wright, 2003) have a clear connection with the smoothness of upper secondary education studies. Learning-oriented students emphasize the mastery of learning new things and contents when referring to their school-related aspirations.…”
Section: Theoretical Background: Studies On Smooth Study Paths In Uppmentioning
confidence: 99%
“…Self-efficacy correlates positively with academic performance (e.g. Bong, 2001;Gore 2006;Chemers, Hu, & Garcia, 2001;Lane & Lane, 2001), academic persistence (Wright, Jenkins-Guarnieri & Murdock, 2013) and achievement for undergraduate students in science and engineering courses (Brown, Lent, & Larkin, 1989;Lent, Brown, & Larkin, 1984, 1986Multon, Brown, & Lent, 1991). In addition, Khezri azar, Lavasani, Malahmadi, and Amani (2010) report a direct effect of self-efficacy on mathematics outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…High academic performance is linked with increased self-confidence and presumably it enhances students to accept greater responsibility for successful completion of tasks (Zimmerman, & Kitsantas, 2005). Some authors believe that students with higher self-efficacy achieve higher levels, because they are able to deal with cognitive demands more efficiently (Lane, & Lane, 2001), attempt to focus on master goals (Hsieh, Sullivan, & Guerra, 2007), perceive their learning as challenges/tasks that are interesting and valuable and apply reasonable learning strategies (Greene et al, 2004). McIlroy et al (2015) relying on results of researches consider self-efficacy the strongest predictor of academic results and its direct influence on academic achievement.…”
mentioning
confidence: 99%